Confidence limits in the oxygen transport parameters of the (La0.8Sr0.2)(Cr0.2Fe0.8)O3-δ determined by the isotopic exchange, depth profiling method - Chater,RJ (2015)
The polycrystalline oxide (La0.8Sr0.2)(Cr0.2Fe0.8)O3-δ is a mixed ionic and electronic conductor of a type called "acceptor-doped transition metal oxide" that has been explored for application as an electrode material in SOFC and other electrochemical devices working at intermediate to high temperatures (500°C to 900°C). The isotopic exchange, depth profiling method allows both bulk oxygen transport parameters, the diffusion coefficient, D(T) and surface reaction coefficient, k(T), to be determined simultaneously once an appropriate solution of the diffusion equation has been identified. Error assessment of (D,k) through the numerical fit process is quantified for the variances that are used as weights in extracting the transport activation energies from the corresponding Arrhenius plots. As the dataset is generally small for a single anneal ambient composition, standard statistical F and t-tests are used and the 95% confidence limits reported that are essential for comparison between datasets.